Clinical trial of ofloxacin alone and in combination with dapsone plus clofazimine for treatment of lepromatous leprosy. - Ji, B (1994)
Twenty-four patients with newly diagnosed lepromatous leprosy were allocated randomly to three groups and treated for 56 days with 400 mg of ofloxacin daily, 800 mg of ofloxacin daily, or 400 mg of ofloxacin, 100 mg of dapsone, and 50 mg of clofazimine daily plus 300 mg of clofazimine once every 28 days. The patients in all three groups demonstrated remarkable clinical improvements, accompanied by rapid decline of the morphological index in skin smears during treatment. More than 99, > 99.99, and > 99.99% of the viable Mycobacterium leprae organisms had been killed by 14, 28, and 56 days of treatment, respectively, as measured by inoculation into the footpads of immunocompetent and nude mice of organisms recovered from skin biopsy specimens obtained before and during treatment. Mild to moderate elevations of the serum glutamic pyruvic transaminase level were observed in four patients, all after 28 days of treatment, which returned to normal after the trial had been completed. Clinical improvement, bactericidal activity, and hepatotoxicity did not differ significantly among the three groups. Ofloxacin displayed powerful bactericidal activity against M. leprae in leprosy patients and may be an important component of new multidrug regimens for the treatment of leprosy. Its optimal dosage appears to be 400 mg daily, and combination with dapsone and clofazimine does not enhance its activity.